Mckinsey's Seven S Service Model for Sub-district Integrated Administration Services in Gayo Lues District - Wahyuni, Ilis Matri; Abubakar, Muhammad Bin; Wulandari, Florentina Ratih (Riwayat: Educational Journal of History and Humanities, 2025)
In order to respond paradigm development policy public service Local Government to realize good governance, pay attention to the needs and demands of the public in public service, with That be taken out Regulation of the Minister of Home Affairs Number 4 of 2010 Concerning Guidelines Service Administration Integrated Sub-district (PATEN). The issuance of PERMENDAGRI Number 4 of 2010 is as a form of giving delegation authority Regency/City against Subdistrict in organizing public service use realize effective and efficient service for society. In which the PATENT is implemented with the objective to increase service quality and bring closer service to society. Research objectives is to analyze service administration integrated in the Blangkejeren sub-district, Gayo Lues Regency. Theory in this study focuses on the use of McKindsey's Seven S service model. Research Methods use qualitative approach. Research results show that Strategy, refers to clear and directed planning to overcome problems in PATEN services. Structure organizations must also be repaired. The structure in question covers the distribution of clear tasks between officers and work units in the sub-district office. System becomes an important aspect in the implementation of PATEN. The operational system used must be integrated with modern technology to speed up the administrative process and make it easier supervision. Shared Values or mark together need to be implanted among all over parties involved. Values like integrity, professionalism, and public service orientation must become the runway in the implementation of the PATEN. Style or style of leadership in the subdistrict office must be capable of supporting change. Adaptive and innovative leaders are required to push for quality service improvement. Staff or source Power man must be noticed from the aspect of quantity and quality. Skills or skills officers need to be improved in a sustainable way. Ability in using technology, understanding to procedure administration, as well as communication skills are things to do controlled by the PATEN officer